Empirical investigation of consumers' intentions to shop online in urban China. - Bu, Xiao Qiu. (2008)
The objectives of the study were: 1) to increase understanding of Chines consumers’ perceptions towards online shopping; 2) to investigate the factors that influence Chinese consumers’ intention to shop online and the relative importance of the factors. In addition, we compared the behavior of consumers from larger and smaller urban areas (i.e, Beijing vs. Chengdu) to capture potential regional differences.